Geotourism potential at Silam Coast Conservation Area (SCCA) Silam, Sabah - Zulherry Isnain; Junaidi Asis; Hazerina Pungut; Sanudin Tahir; Baba Musta; Hardianshah Saleh (Universiti Malaysia Sabah, 2017)
A research has been conducted at Silam Coast Conservation Area (SCCA) to evaluate the geotourism potential of the geological heritage resources. The study area is located at Silam, Lahad Datu, in the eastern part of Sabah. The SCCA and surrounding area were made up of igneous and sedimentary rocks of ultramafic, gabbro, amphibolite, basaltic dykes, plagiogranites and basaltic rocks capped by red radiolarian chert. It is also known as the Darvel Bay Ophiolite Complex which represents the ophiolitic sequence of oceanic crust that formed during Jurassic to Cretaceous around 150-80 million years ago. In SCCA area, only pillow basalt, lava basalt, chert and minor occurrence of basalt dyke were present. Mid-Miocene tectonic event deformed and uplifted the rock unit. SCCA is a coastal area which also covers few small islands namely Tabun Island and Saranga Island to the northeast of the conservation area in Darvel Bay. The geomorphology and geologic features contribute to the aesthetic values of the area that enhances the scientific values. Two potential geosites have been identified which are Tabun-Saranga islands and Pandanus-Ara beaches that hold unique features of remnant cliff, wave-cut cliff, faults, caves, stacks, tafoni, headland, pocket beach, colluvial beach deposit and remnant of raised coral colonies. Development of this geosites could lead to conservation for sustaining the geological heritage resources as well as contributing to the state’s economy and tourism industry.